Understanding Firms' Inflation Expectations Using the Bank of Canada's Business Outlook Survey - Simon Richards; Matthieu Verstraete (Center for Economic Studies and ifo Institute (CESifo), 2016)
Inflation expectations are a key determinant of actual and future inflation and thus matter for the conduct of monetary policy. We study how firms form their inflation expectations using quarterly firm-level data from the Bank of Canada's Business Outlook Survey, spanning the 2001 to 2015 period. The data are aggregated to construct an inflation expectations index. Results based on the index suggest that expectations are not consistent with the rationality assumption but are, still, more complex than purely adaptive expectations. Firms' own unique experiences, such as the dynamics of the prices they expect to pay (wages/inputs), significantly influence aggregate expectations. Expectations are also found to be significantly and positively correlated with movements in oil prices. Most of the preceding results hold at the firm level. The estimation of structural shift specifications suggests that inflation expectations in Canada have drifted downward since the Great Recession. However, the data do not suggest that Canadian businesses' expectations have become unanchored.
Keywords: C10; C20; C25; D21; D84; E31; E52; E58; 330; credibility; central bank research; econometric and statistical methods; firm dynamics; inflation targets; inflation and prices; monetary policy framework